LARGS Performance Integrations in A Laundry Supply Chain - Saputra, Rafly Galih; Saputri, Evieana R.; Kusumadewi, Hermala (Syntax Literate, 2024)
This research is conduct with the object to observe whether that lean, agile, resilience, green, and sustainable can be applied into a laundry supply of supply chain management. Literature review are reviewed to build a foundation regarding SCM to achieve the objectives. Model of lean, agile, resilience, green, and sustainable are built on the theoretical review of literature. The novelty of this research is to classify scheme of a laundry supply chain paradigm in SCM was developed. The result indicates that lean, agile, resilience, green, and sustainable have a important role to achieve successful performance, and customer satisfaction.